LEARNING MODEL OF KITAB AL-JURUMIYAH AT THE ISLAMIC BOARDING SCHOOL - Latipah Harahap; Darwin Zainuddin (Sean Institute, 2023)
This article aims to obtain information about the Learning Model of Kitab Al-Jurumiyah at Pondok Pesantren. This research is a library research (Library Research). The literature method is a suitable method in this study. Because in this case library sources such as books and journals both nationally and internationally will be used to collect various data related to instilling tawhid values in Arabic language learning . From the presentation, it can be concluded that there are several methods that can be used to convey knowledge from the book of Al-Jurumiyah, including: Al-Qiyasiyah Model (Analogy), Istiqroniyah Model (Induction), Sample Model, Whole Text Model.